Defect-gradient-induced Rashba effect in van der Waals PtSe2 layers - Junhyeon Jo; Jung Hwa Kim; Choong H. Kim; Jaebyeong Lee; Daeseong Choe; Inseon Oh; Seunghyun Lee; Zonghoon Lee; Hosub Jin; Jung-Woo Yoo (Nature Communications, 2022)
Materials with strong Rashba-type spin-orbit coupling hold promise for spintronic applications and the investigation of topological phases of matter. Here, the authors report a method to generate layer-by-layer defect gradients in a van der Waals material, inducing broken spatial inversion symmetry and Rashba effect in the engineered layers.